2007
DOI: 10.1111/j.1540-8159.2007.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Lesion Sizes and Tissue Temperatures During Catheter Cryoablation

Abstract: Lesion sizes and tissue temperatures during catheter cryoablation are related to convective warming, electrode orientation, electrode contact pressure, and any of the following: electrode size, catheter refrigerant flow rate or electrode temperature. However, electrode temperature may be a poor predictor of lesion size and tissue temperature for a given catheter size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 18 publications
(70 reference statements)
4
51
0
Order By: Relevance
“…RF ablation of more myocardial tissue in the atria, such as in PV isolation, is expected to have much higher cTn levels [10][11][12][20][21][22][23][24][25]. Previous clinical studies reported contrasting data, in the setting of AF ablation, on cardiac biomarkers levels after cryoballoon ablation compared to RF ablation [7,[13][14][15][16][17][18][19]26]. Kuhne et al [7] reported higher post procedural cTnT levels in RF group vs. cryoballoon group.…”
Section: Previous Studiesmentioning
confidence: 96%
See 2 more Smart Citations
“…RF ablation of more myocardial tissue in the atria, such as in PV isolation, is expected to have much higher cTn levels [10][11][12][20][21][22][23][24][25]. Previous clinical studies reported contrasting data, in the setting of AF ablation, on cardiac biomarkers levels after cryoballoon ablation compared to RF ablation [7,[13][14][15][16][17][18][19]26]. Kuhne et al [7] reported higher post procedural cTnT levels in RF group vs. cryoballoon group.…”
Section: Previous Studiesmentioning
confidence: 96%
“…First studies focused on RF lesion and it has been demonstrated that cTnI and cTnT are more sensitive and specific than CK--MB for the diagnosis of myocardial injury after RF ablation [5,6]. It has also been showed that the rise of biomarkers and the extent of myocardial damage after RF catheter ablation depend on the number of RF pulses and site of ablation [12][13][14][15][16]19]. A lower cTn level is expected after RF of focal area with few RF lesions.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be expected that the 6 mm tip or the 8 mm tip cryoablation catheter would create larger lesion dimensions. Also, there are far more combinations of variables that could potentially be evaluated, including higher power and temperatures for radiofequency ablations, longer duration of either cryoablation or radiofrequency lesions, catheter tip orientation, time to cool the cryoablation electrode or time to cryoablation electrode rewarming 36,37 …”
Section: Editorial Commentmentioning
confidence: 99%
“…23 Wood et al performed in-vitro experiments with 7F, 4-mm and 9F, 8-mm tip catheters and found that cryoablation lesion sizes and tissue temperatures are related to convective warming, electrode orientation, electrode contact pressure, and any of the following: electrode size, catheter refrigerant flow rate, and electrode temperature. 24 d'Avila et al reported that endocardial and epicardial cryolesions created in a normal caprine model by focal cryoablation for 4 min with a 7F, 6-mm tip catheter at a mean temperature of -77±2°C for endocardium and -81± 3°C for epicardium were similar in size and depth (endocardium: 9.7±0.4 mm long, 7.3±1.4 mm wide, 4.8±0.2 mm deep; epicardium: 10.2±1.4 mm long, 7.7±2.0 mm wide, 4.6±0.9 mm deep). 25 They also reported that the epicardial cryolesion created in a porcine chronic infarct model by linear cryoablation with a 7F, 30-mm tip catheter at a mean temperature of -84±6°C for 4 min was 36.5±7.8 mm long, 8.2±1.3 mm wide, and 6.0±1.2 mm deep.…”
Section: Table Catheter-based Cryoablation and Lesion Characteristicsmentioning
confidence: 99%